The effects of soil freeze–thaw processes on water and salt migrations in the western Songnen Plain, China - Yan Qin (Nature Portfolio, 2021)
Abstract Seasonally freeze-thaw (FT) processes affect soil salinisation in cold and arid regions. Therefore, understanding the mechanisms behind soil salinisation during winter and spring is crucial for management strategies effectively alleviating this. This study aimed to explore the soil FT characteristics and their influences on soil water and salt migrations to clarify the underlying mechanism of the springtime soil salinisation in the western Songnen Plain, China. The spatiotemporal distributions of soil water and salt, frozen depths and soil temperatures were examined at depths of 0–200 cm in three typical landscapes (farmland, Leymus chinensis (Trin.) Tzvel (LT) grassland and alkali-spot (AS) land) from October 2015 to June 2016. Results indicated that the strongest freezing process occurred in AS land, which was characterised by the deepest frost depth (165 cm) and highest freezing rate (3.58 cm/d), followed by LT grassland, and then farmland. The freeze-induced upward redistribution and enrichment of soil water and salt caused the rise and expansion of the soil salification layer, which was the main source of explosive accumulations of surface salt in springtime. Therefore, the FT processes contributed to the surface soil salinisation and alkalisation. Landscapes also affected soil water and salt migrations during FT processes, with the trend being AS land > LT grassland > farmland.